Stability of kaolin particles subjected to elevated temperatures using various dispersing agents. (April 2020) - Shakrani, S A; Ayob, A; Ab Rahim, M A; Alias, S
Abstract: The stability of kaolin particles is largely influenced by nature and the behaviour of dispersing agents introduced to the system. This study analysed the size of kaolin particles subjected to elevated temperatures by using various dispersing agents such as ultrapure water (UPW), acetone (Ace) and sodium hydroxide (NaOH). It was found that kaolin particles in UPW formed a stable dispersion compared to particles in Ace and NaOH without further aggregation. Interestingly, kaolin particles under UPW, Ace, and NaOH dispersants had a strong affinity for water and can be classified as possessing hydrophilic behaviour. The mean size of kaolin particles was reduced under UPW and Ace dispersion but increased under NaOH suspension. Under UPW dispersion, kaolin particles ranged from 141.8nm to 5560nm, creating a mid-range monodisperse size distribution (0.08 < PDI < 0.7) without any presence of agglomeration due to high potential energy barrier and electrostatic repulsion. Kaolin particles subjected to NaOH dispersant produced a narrow distribution of particle sizes ranging from 295.3nm to 1106nm but appeared to agglomerate because of Van der Waals interactions. In contrast, the Ace dispersant produced a very broad polydisperse particle size distribution (PDI > 0.7) of greater than 10μm in kaolin with a little aggregation but lacking consistency in terms of stability. However, all dispersants contributed to the kaolin particles dispersion but UPW shown more stability dispersion due to increase in number of hydroxyl groups in dispersant molecule. In conclusion, this simple and low cost methodology can be useful in characterising kaolin particle sizes with limited resources.